Perancangan Basis Data Sistem Informasi Smart Kos Berbasis ERD, CDM, dan PDM - Maulida Nabil Alifah; Kenzia Zahwa Eddyputri; Nabila Najma Zhafirah; Zatin Niqotaini (Jurnal Nasional Teknologi Informasi dan Aplikasinya, 2026)
Manual management of boarding houses remains a widespread problem faced by many boarding house owners in Indonesia. Various issues such as errors in recording tenant data, unmonitored late rent payments, difficulties in monitoring room status, and undocumented facility complaint communications present real challenges in conventional boarding house management. This study aims to design and model a database for the Smart Kos Information System as an integrated digital solution. The design was carried out using Entity Relationship Diagram (ERD), Conceptual Data Model (CDM), and Physical Data Model (PDM) approaches to produce a structured and consistent database model. The designed entities cover tenant data, rooms, rent payments, and facility damage reports.